2014
DOI: 10.4103/1450-1147.139138
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Scan Strategy and Outcomes in Chest Pain Patients Value of Stress Testing with Dipyridamole or Adenosine

Abstract: Objective:To update the prognostic value of scan strategy with pharmacological stress agent in chest pain (CP) patients presenting with normal electrocardiography (ECG) and troponin.Methods:Two consecutive nonrandomized series of patients with CP and negative first-line workup inclusive of serial ECG, serial troponin, and echocardiography underwent myocardial perfusion imaging single photon emission computed tomography (SPECT) in the emergency department. Of 170 patients enrolled, 52 patients underwent dipyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…These pharmaceutical agents are currently used in patients unable to exercise to evaluate myocardial perfusion with different diagnostic accuracy. A recent study conducted by Conti et al showed that adenosine-based SPECT had better sensitivity and specificity than dipyridamole-based SPECT (20) while diagnostic value of adenosine-based SPECT was found to be similar compared to exercise-based SPECT (21) . We also used intravenous adenosine infusion to produce coronary vasodilatation in 66% of the study population.…”
Section: Discussionmentioning
confidence: 98%
“…These pharmaceutical agents are currently used in patients unable to exercise to evaluate myocardial perfusion with different diagnostic accuracy. A recent study conducted by Conti et al showed that adenosine-based SPECT had better sensitivity and specificity than dipyridamole-based SPECT (20) while diagnostic value of adenosine-based SPECT was found to be similar compared to exercise-based SPECT (21) . We also used intravenous adenosine infusion to produce coronary vasodilatation in 66% of the study population.…”
Section: Discussionmentioning
confidence: 98%
“…Adenosine based MPS was proven to have higher diagnostic ability than dipyridamole based protocols, however it had equal diagnostic ability compared to exercise based protocols [24,25]. Thus, to obtain measurable and similar level of physical stress, we applied ETT to induce coronary ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adenosine can significantly expand normal coronary arteries, although it does not significantly influence the increase in arterial blood flow in stenosis. The blood flow resistance is lower in the non-ischemic zone compared with that in the ischemic areas into the non ischemia areas are through the collateral circulation reflux to the non-ischemia area, which is namely the transverse vascular steal phenomenon (16). Furthermore, adenosine increases the coronary blood flow, which not only increases the pressure difference cross the stenosed coronary arteries, but also decrease the distal blood flows of stenosed vessels, and cause the blood flows of epicardium increasing and blood flows of endocardium decreasing, this is known as the longitudinal vascular steal phenomenon.…”
Section: Discussionmentioning
confidence: 99%